Mg‐doped α‐Ga2O3 Nanorods for the Construction of Photoelectrochemical‐Type Self‐Powered Solar Blind UV Photodetectors and Underwater Imaging Application - Xin Zhou; Lijuan Ye; Lai Yuan; Dan Zhang; Hong Zhang; Di Pang; Yan Tang; Honglin Li; Wanjun Li; Heping Zeng (Advanced Science)
Abstract Underwater imaging technologies are increasingly crucial for environmental monitoring and resource exploration. However, the development of advanced photodetectors for such applications faces significant challenges, including interference from ambient visible and infrared light, adaptation to underwater environments, and cost‐effectiveness. Photoelectrochemical‐type solar‐blind photodetectors (PEC‐SBPDs) based on wide bandgap semiconductors have shown great promise in overcoming these challenges. Here, a novel approach to enhance the performance of α‐Ga2O3‐based PEC‐SBPDs is presented for underwater imaging through Mg‐doping. By employing a low‐cost hydrothermal synthesis technique, Mg‐doped α‐Ga2O3 nanorod arrays are fabricated, which induces the formation of VO‐MgGa complexes that enhances the interfacial catalytic activity and improves the transport of photogenerated carriers. The optimized PEC‐SBPDs exhibits a remarkable 435% increase in photocurrent response compared to undoped α‐Ga2O3, with a peak responsivity of 34.54 mA W−1. A 5 × 5 PEC‐SBPD array based on Mg‐doped α‐Ga2O3 nanorods is successfully demonstrated for underwater solar‐blind imaging, achieving clear and efficient imaging in challenging underwater conditions. This study not only highlights the superior performance of Mg‐doped α‐Ga2O3 in underwater environments but also opens new avenues for the development of high‐performance self‐powered photodetectors in imaging, sensing, and other related applications.